Pengaruh Collaborative Learning dan Motivasi terhadap Kinerja Pembelajaran berbasis Learning Management System - Suteja, Bernard Renaldy; Zakaria, Teddy Marcus (Jurnal Teknik Informatika dan Sistem Informasi, 2025)
This study analyzes the influence of Collaborative Learning Object Materials (LOM) and learning motivation on student performance in an Internet of Things (IoT) course using blended learning. The research was conducted using the Maranatha Online Learning (MORNING) platform, a Moodle-based Learning Management System (LMS). A flipped classroom model was implemented, integrating synchronous and asynchronous learning strategies. Path analysis was used to evaluate the relationship between LOM interaction, learning motivation, and learning outcomes. The results indicate that LOM interaction (B=0.656, p=0.000003) and learning motivation (B=0.341, p=0.005318) have a significant influence on learning performance (R²=0.648). Thus, this study demonstrates the potential of collaborative and motivational strategies in enhancing student engagement and performance in blended learning.